Homogeneous Hydrogenation of Carbon Dioxide - Jessop, Philip G; Ikariya, Takao; Noyori, Ryoji (Chemical reviews, 1995)
The simplest and most studied reactions of carbon dioxide--the catalytic reactions with H2 in the presence or absence of other reactive species--are described, and the mechanisms of homogeneously catalyzed reactions will be emphasized. Systems with water or supercritical carbon dioxide as reaction media show the most promise.